2020
DOI: 10.3390/biology9100311
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of P4 + eCG Estrus Induction Protocol during the Deep and the Transition Anestrous Period on the Reproductive Performance of Crossbred Dairy Goats

Abstract: Seasonal reproduction restricts the offering of goat commodities across the year. Therefore, it is crucial to improve diverse strategies to induce the reproductive response in goats during the anestrus stage. The effectiveness of a short P4 + eCG-based estrus induction protocol during both the deep anestrous (March) or the reproductive transition period (June) upon the reproductive performance of crossbred dairy goats was assessed. Adult, anestrous, 24–30-month- old dairy crossbred (Saanen–Alpine–Nubian × Crio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…From d −5 to d +15 (i.e., 23 March to 12 April), both groups of goats grazed from 09:00 to 19:00 h. The sampling process of the feed leftovers was carried out by taking 10 samples (i.e., 50 g each) along the feeding line and subsequently analyzed the samples' chemical and physical composition in the Chemistry Laboratory of the university (Table 1). 3 3.5…”
Section: Animals and Their Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…From d −5 to d +15 (i.e., 23 March to 12 April), both groups of goats grazed from 09:00 to 19:00 h. The sampling process of the feed leftovers was carried out by taking 10 samples (i.e., 50 g each) along the feeding line and subsequently analyzed the samples' chemical and physical composition in the Chemistry Laboratory of the university (Table 1). 3 3.5…”
Section: Animals and Their Managementmentioning
confidence: 99%
“…In both ovaries, the number of corpora lutea, as evidence of ovulation, was categorized as single, double, or triple. Every CL was measured to determine its luteal tissue volume (V) by using the following formula: V = 4/3 × π × r 3 . The radius (r) was calculated using the formula r = (L/2 + A/2)/2, where L = length, and A = width [28].…”
Section: Response Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult Saanen goats living in tropical condition present accentuated anestrus during spring; however, during early summer, social interactions with males or cycling females may induce, in different degrees, the return to cyclicity (Balaro et al, 2019). During this transition season, the use of hormonal protocols leads to better results in reproductive rates, since cyclicity is homogenized (Alvarado-Espino et al, 2016;Véliz-Deras et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Muñoz et al (2019) showed that the presence of the sexually active male was enough to induce a second ovulation after an induced luteolysis in estrous induced does. During transition season, Véliz-Deras et al (2020) demonstrated that NM presented higher pregnancy rates (42% x 20%) than Artificial Insemination (AI) even when it was performed with fresh semen. That being so, the presence of an active male during the second synchronization may improve synchronization results, especially for females that did not undergo eCG treatment.…”
Section: Introductionmentioning
confidence: 99%